Childhood tuberculosis: a possible bioarchaeological cas in Tierra del Fuego (Argentina) - Pandiani, Cynthia Daniela (2023)
Tuberculosis is a chronic infectious disease widely studied in archaeological human remains due to its relevance to past and present populations. Previous studies have reported cases consistent with the disease in the Southern Patagonia region, although mainly in adult individuals. However, the impact of tuberculosis on non-adult individuals is less known. This study presents a possible case of tuberculosis in a nearly complete and well-preserved skeleton of a non-adult individual (MFM 851), with estimated age at 9-11 years old at the time of death, from the province of Tierra del Fuego, Argentina. Lesions that could be associated with tuberculosis were recorded and described, including their location, laterality, type of bone reaction (lytic, osteolytic, or mixed), and formation of new bone (woven, lamellar, or mixed). As a result, proliferative periosteal reactions were identified on the visceral surface of the vertebral end of the ribs (between the 3rd and 9th on the right side and between the 3rd and 11th on the left side). Woven bone formations were also recorded on the anterior surface of the distal and proximal thirds of the left femur, the anteromedial surface of the distal third of both tibias, and the lateral-posterior surface of the proximal and distal thirds of both fibulas. Following the Istanbul Protocol, the observed lesions are highly consistent with tuberculosis, active at the time of death. These findings provide evidence that non-adults were exposed to the development of the disease even prior to Indigenous-European contact in the region.